Burocracia e vida moral: um estudo sobre as experiências morais nas práticas de auditores públicos no estado da Paraíba - Rosas, Ana Karolina Ramalho de Araújo (2020)
In recent years there has been an increase in the social sciences of studies about the relationship between bureaucracy and moral values, especially in the area of sociology and anthropology of the State, in which the number of ethnographic research on the moral experiences of individuals has been increasing. Its greater relevance derives from the fact of the growing need to know not only the dynamics of social facts, but also the ideas and values of social actors, their moral meanings. In order to contribute to the sociological knowledge in this area, this study analyzes the moral experiences of the practices of public auditors in the State of Paraíba. The central idea is to understand the moral dimension of control and transparency practices and to empirically investigate the ways in which these values are being incorporated into the daily lives of public agents. The present object will be explored from an approach of the sociology of morals and of an anthropology of the State, aiming to understand the logics of power that are reaffirming in the ideal of a transparent State. We analyzed two empirical cases of local audit experience, at the General Controller of the State of Paraíba and at the General Controller of the Municipality of João Pessoa. We argue that it is necessary to analyze the forms of government technologies based on the daily routine of bureaucracies and disputes between the different fields of power, with a view to technical ideals and moral and political values.